Public Rental Housing Governance in Urban China: Essence, Mechanisms and Measurement - Yan, Juan (A+BE | Architecture and the Built Environment, 2021)
Recently, Chinese Public Rental Housing (PRH) provision has witnessed a shift from ‘government’ to ‘governance’: policy making shifted from government steering to mixed forms involving government, market and civic actors to pursue effective and fair policies. In the meantime, this new-era PRH governance is credited with mixed results. However, the existing studies fail to describe the mechanisms underlying this new-era governance of PRH with the rising involvement of market actors and those in civil society and whether the new-era governance is considered to be effective, achieving the objective of stability. Therefore, this PhD research aims to fill the two research gaps through building a better understanding of the PRH governance in the current Chinese context and evaluating PRH governance. To fulfil this aim, this dissertation is underpinned by a theoretical foundation from the governance perspective and adopts a mixedmethod approach with quantitative and qualitative data in the study of Chinese PRH provision. The dissertation reveals the essence of the current Chinese PRH governance by bringing forth a governance model and shows the structures and mechanisms for non-governmental actors to play a role in the governance of PRH. The dissertation also shows the perceived governance outcomes from tenants’ perspective and demonstrates two main governance challenges of Inclusionary Housing, a newly introduced instrument adopted in the Chinese PRH governance. Based on the results, this PhD research theoretically and empirically contributes to the housing governance literature.